Pengembangan Media Layanan Bimbingan Kelompok Permainan Ular tangga Truth or Dare untuk Memfasilitasi Kepercayaan Diri Siswa SMAN 7 Pekanbaru - Adinda Afrilian; Khairiyah Khadijah; Isnaria Hayati (Conseils : Jurnal Bimbingan dan Konseling Islam, 2026)
Self-confidence is an essential aspect of students’ personal development, influencing their ability to socialize, make decisions, and face challenges both in school and everyday life. However, many students still exhibit low self-confidence, such as fear of speaking in public and hesitation to express opinions. Therefore, engaging and enjoyable media are needed to help students become more open and motivated to develop their self-confidence through group guidance services. This study is a Research and Development (R&D) project aimed at producing a group guidance medium in the form of a Snakes and Ladders Truth or Dare game to enhance students’ self-confidence. The trial results indicated that the media received positive responses; students became more active, enthusiastic, and confident in expressing their opinions and interacting with others. Thus, the Snakes and Ladders Truth or Dare game is considered an effective and innovative medium for facilitating the development of students’ self-confidence in schools.